Association of Preoperative Plasma D-Dimer and Fibrinogen and Osteosarcoma Outcome - Pu, Yanchuan; Wang, Jin; Wang, Jianshu; Wang, Shizhong (Frontiers in Oncology, 2022)
Objective: We aimed to evaluate the utility of preoperative D-dimer and plasma fibrinogen (PF) levels as useful markers for predicting the clinical value of patients with osteosarcoma. Methods: 145 enrolled patients with osteosarcoma were studied retrospectively. We determined the critical values of D-dimer and PF by receiver operating characteristic curve analysis. Cox regression analysis was used to assess prognostic role of the D-dimer and PF levels among osteosarcoma patients. Results: The critical values of D-dimer and PF were calculated to be 0.46 µg/mL and 3.34 mg/mL, respectively. Upregulation of D-dimer and PF showed positive correlations with a higher clinical stage, tumour metastasis and recurrence. Survival curve results confirmed that osteosarcoma patients with higher levels of D-dimer and PF predicted worse overall survival (OS) and progression-free survival (PFS). Moreover, only a high D-dimer level was associated with a shorter OS (P = 0.013) and PFS (P = 0.042) in both the univariate and multivariate analysis. Conclusion: Elevated preoperative D-dimer levels are correlated with aggressive clinicopathological features and poor survival outcomes, which indicates that assessment of the D-dimer could be a useful prognostic marker in osteosarcoma.